Orientation Of Leadership Supervision On Employee Discipline - Juliana, Encep; Khumayah, Siti; Rahmayanti, Rahmayanti (ann4publisher@gmail.com, 2024)
This study aims to find out the role of leadership in supervising employee discipline located in the Cirebon Class II KSOP Office. The method used is qualitative, including observation, interviews, and documentation studies as research data sources. This article discusses the analysis of leadership supervision oriented toward employee discipline and reveals the driving and inhibiting factors of the supervision process in the field. The conclusion obtained from this study is that leadership supervision is carried out through monitoring employee attendance administration, periodic discipline evaluation, personal employee coaching, and coordinating with the personnel department in improving employee discipline, which is already optimal, but still found employee discipline that is not per the rules. The informal leadership communication style is a supporting factor in supervision, but on the other hand, this does not cause a positive change in the attitude of discipline in employees.